2020
DOI: 10.3390/ijms21218072
|View full text |Cite
|
Sign up to set email alerts
|

Activation of RAS Signalling is Associated with Altered Cell Adhesion in Phaeochromocytoma

Abstract: Phaeochromocytomas and paragangliomas (PPGLs) are neuroendocrine catecholamine-producing tumours that may progress into inoperable metastatic disease. Treatment options for metastatic disease are limited, indicating a need for functional studies to identify pharmacologically targetable pathophysiological mechanisms, which require biologically relevant experimental models. Recently, a human progenitor phaeochromocytoma cell line named “hPheo1” was established, but its genotype has not been characterised. Perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Recent studies have identified ancillary driver mutations in ATRX (Fishbein et al, 2015), KIF1B, and NF1 (Evenepoel et al, 2017) in patients harboring SDHB mutations. This is congruent with recently discovered mutations in KIF1B and NRAS genes in hPheo1 cells (Rossitti et al, 2020). In addition to the germline driver SDHB mutations, ancillary mutations in hPheo1 create the opportunity to study malignant PC behavior.…”
Section: Discussionsupporting
confidence: 75%
“…Recent studies have identified ancillary driver mutations in ATRX (Fishbein et al, 2015), KIF1B, and NF1 (Evenepoel et al, 2017) in patients harboring SDHB mutations. This is congruent with recently discovered mutations in KIF1B and NRAS genes in hPheo1 cells (Rossitti et al, 2020). In addition to the germline driver SDHB mutations, ancillary mutations in hPheo1 create the opportunity to study malignant PC behavior.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, subsequent evaluation of DNA from the patient’s PCC tumor and hPheo1 cell line detected the pathogenic mutation in the NF1 gene, NM_001042492.3 (NF1): c.4330A>G (p.Lys1444Glu) ( Figure 3B ). A second variant identified in primary PCC and hPheo1 was KIF1B variation T827I (c.2480C > T, rs121908162), which is predicted to be benign by PolyPhen-2 ( 24 ). Other mutation, previously reported for hPheo1 line, in addition to KIF1B , also includes NRAS Q61K ( 24 ) which was not detected in the patient’s tumor DNA, and may represent an adaptation of the cell line in culture (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A second variant identified in primary PCC and hPheo1 was KIF1B variation T827I (c.2480C > T, rs121908162), which is predicted to be benign by PolyPhen-2 ( 24 ). Other mutation, previously reported for hPheo1 line, in addition to KIF1B , also includes NRAS Q61K ( 24 ) which was not detected in the patient’s tumor DNA, and may represent an adaptation of the cell line in culture (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The “trypsin-sensitive cells” was generated by transferring cells detached by 1 min trypsinization to a new dish. The “trypsin-resistant cells” were generated by continuing the culturing of the starting population for 30 min, washing with PBS and discarding the detached cells [ 33 , 50 ].…”
Section: Methodsmentioning
confidence: 99%